2007
DOI: 10.1002/rcm.3251
|View full text |Cite
|
Sign up to set email alerts
|

Capillary hydrophilic interaction chromatography/mass spectrometry for simultaneous determination of multiple neurotransmitters in primate cerebral cortex

Abstract: A diverse array of neurotransmitters and neuromodulators control and affect brain function. A profound understanding of the signaling pathways and the neural circuits underlying behavior is therefore likely to require the tracking of concentration changes of active neurochemicals. In the present study, we demonstrate the feasibility of a method allowing the simultaneous determination of the concentrations of six neurotransmitters: acetylcholine, serotonin, dopamine, g-aminobutyric acid (GABA), glutamate and as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 40 publications
2
65
0
Order By: Relevance
“…The highly volatile organic mobile phase used in HILIC facilitates the desolvation and compound ionization in the electrospray process and provides increased ESI-MS sensitivity (Kebarle, 2000). The separation of ACh based on HILIC has been conducted with polar stationary phases such as silica (Grumbach et al, 2004), aminopropyl, amide (Guo, 2005), polyhydroxyethyl aspartamide (Wang et al, 2008;Zhang et al, 2007b) or diol (Uutela et al, 2005). Uutela et al (2005) developed a HILIC method in which a diol column was used, not only for the separation of ACh, choline and the IS, but also for the separation of the analytes from inorganic salts and endogeneous compounds within a chromatographic run time of 10 min.…”
Section: Liquid Chromatography Mass Spectrometry Chromatographymentioning
confidence: 99%
“…The highly volatile organic mobile phase used in HILIC facilitates the desolvation and compound ionization in the electrospray process and provides increased ESI-MS sensitivity (Kebarle, 2000). The separation of ACh based on HILIC has been conducted with polar stationary phases such as silica (Grumbach et al, 2004), aminopropyl, amide (Guo, 2005), polyhydroxyethyl aspartamide (Wang et al, 2008;Zhang et al, 2007b) or diol (Uutela et al, 2005). Uutela et al (2005) developed a HILIC method in which a diol column was used, not only for the separation of ACh, choline and the IS, but also for the separation of the analytes from inorganic salts and endogeneous compounds within a chromatographic run time of 10 min.…”
Section: Liquid Chromatography Mass Spectrometry Chromatographymentioning
confidence: 99%
“…The striatum sample is prepared using 16 L solution per 1 mg of tissue. Each QAC was detected with signal to noise ratio 10. used for analysis of acylcarnitines but not free carnitine, acetylcholine or choline [30], while HILIC-MS allowed polar QACs such as acetylcholine and choline to be separated and detected [13,14]. Although a recent study has shown that acetylcarnitine and palmitoylcarnitine could be analyzed using HILIC-MS [31], the elution times of the two QACs were short and very close, reflecting the low separation and peak capability of HILIC-MS for a large number of QACs, in particular for hydrophobic ones.…”
Section: Rp-hilic-ft-ms Analysismentioning
confidence: 99%
“…This hydrophobicity diversity poses challenges for the LC-MS analysis. Currently, the separation of QACs of high polarity, such as choline, acetylcholine, carnitine and acetylcarnitine, are commonly conducted using hydrophilic interaction chromatography (HILIC)-MS [13,14], ion-exchange chromatography [15,16], or ionpairing reversed phase (RP) chromatography [17][18][19]. To separate carnitines of both low and high polarities, pre-column derivatization has been used to improve their separation on common RP columns [20].…”
Section: Introductionmentioning
confidence: 99%
“…The preparation of capillary columns was adopted and modified from Zhang et al [23]. To prevent the packing material from spilling out of the column a frit was formed at one end by in situ free radical polymerization modified from Viklund et al [27].…”
Section: Fabrication Of Capillary Columnsmentioning
confidence: 99%
“…It already has proved its merits in determining peptides, proteins and small polar molecular compounds in complex matrices [21][22][23][24]. Recent reports demonstrated that HILIC-MS is well suited to determine polar neurotransmitters in EBF offering high sensitivity combined with time-saving procedures for sample preparation [23,25].…”
Section: Introductionmentioning
confidence: 99%